Marketingový mix služeb - Veličková, Daniela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Hlavním předmětem bakalářské práce „Marketingový mix služeb“ je analýza současného stavu a následný návrh na zefektivnění marketingové strategie podniku nabízejícího služby v oblasti tělovýchovy a sportu. Teoretická část se zabývá základními pojmy marketingového mixu služeb souvisejícími s danou problematikou. Analytická část je zaměřena na aktuální stav fitcentra Best Gym Horova. V praktické části jsou představeny konkrétní návrhy a doporučení, díky kterým by mělo dojít k efektivnější marketingové strategii.

The main purpose of the bachelor thesis 'Marketing mix of services' is the analysis of a current situation and a subsequent proposal for efficiency improvement of marketing strategy of a company offering services in a field of physical education and sports. The theoretical part deals with basic terms of service marketing mix which are connected with given problematics. The analytic part of the thesis is focused on current situation of the fitness centre Best Gym Horova. In the practical part specific proposals and suggestions are given. Thanks to them more effective marketing strategy should occur
Marketing Mix of Services
Keywords: marketing; marketingový mix; služby; marketing služeb; marketing sportu; komunikační mix; marketing; marketing mix; services; marketing of services; marketing of sports; communication mix